2021
DOI: 10.3390/pathophysiology28010004
|View full text |Cite
|
Sign up to set email alerts
|

Is an Immunosuppressive Microenvironment a Characteristic of Both Intra- and Extraparenchymal Central Nervous Tumors?

Abstract: In spite of intensive research, the survival rates of patients diagnosed with tumors of the central nervous system (CNS) have not improved significantly in the last decade. Immunotherapy as novel and efficacious treatment option in several other malignancies has failed in neuro-oncology likely due to the immunosuppressive property of the brain tissues. Glioblastoma (GBM) is the most aggressive malignant CNS neoplasm, while meningioma (MNG) is a mainly low grade or benign brain tumor originating from the non-gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…These results suggested that the SULT1E1 + subpopulation in high‐grade meningiomas may directly contribute to the formation of an immunosuppressive environment, which is a common characteristic of aggressive tumors. [ 30 ] Targeting the CSF1‐CSF1R axis has been suggested as a potential treatment strategy for malignant meningiomas, [ 24b ] and combination therapies targeting both CSF1‐CSF1R axis and SULT1E1 + subpopulation may be a more effective immunotherapy for high‐grade meningiomas.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggested that the SULT1E1 + subpopulation in high‐grade meningiomas may directly contribute to the formation of an immunosuppressive environment, which is a common characteristic of aggressive tumors. [ 30 ] Targeting the CSF1‐CSF1R axis has been suggested as a potential treatment strategy for malignant meningiomas, [ 24b ] and combination therapies targeting both CSF1‐CSF1R axis and SULT1E1 + subpopulation may be a more effective immunotherapy for high‐grade meningiomas.…”
Section: Discussionmentioning
confidence: 99%
“…In a 1994 study by Klein et al, where escalating radiation doses were delivered to glioblastoma specimens, exposure to RT was linked to an increase in major histocompatibility complex class I antigen expression, suggesting an increase in cytotoxic T-cell activity against glioblastoma [ 96 ]. Additionally, a recent study by Soltani et al suggested that glioblastomas and low grade meningiomas share similarities in their tumor microenvironments which are associated with immunosuppression [ 97 ].…”
Section: Glioblastoma Treatmentmentioning
confidence: 99%